A history of violence - Cronenberg, David, 1943-; Mortensen, Viggo; Bello, Maria, 1967-; Harris, Ed, 1950-; Hurt, William; Wagner, John, 1949- ([Los Angeles, Calif.] : New Line Home Entertainment, 2006)
A quiet man's family life threatens to fall apart when an act of self-defense thrusts him into the spotlight.
Based on the graphic novel by John Wagner.
Originally released as a motion picture in 2005.
Features: director commentary, deleted scenes with commentary, "Acts of violence" documentary, "The unmaking of scene 44," "Violence's history: U.S. vs. international versions," "Too commercial for Cannes" featurettes.
Viggo Mortensen, Maria Bello, Ed Harris, William Hurt.
MPAA rating: R.
DVD.
Keywords: Wagner, John, -- 1949- -- Film and video adaptations; Criminals -- Drama; Families -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films